MECHANISM OF HYDROCARBON PRODUCTION FROM SYNTHESIS GAS ON THE SURFACE OF A HIGHLY DISPERSED IRON CATALYST (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article studies the mechanism of hydrocarbon production from synthesis gas in the presence of a highly dispersed iron catalyst. The study analyzes the main stages of Fischer-Tropsch synthesis, the activity of the iron catalyst, the influence of carbonyl and carbide phases. Experimental and theoretical results allow us to explain the mechanism of the process of formation of high molecular weight hydrocarbons from synthesis gas. The results of the study are important for creating effective catalysts in the production of alternative fuels and chemical raw materials.